Pengaruh Struktur Aset, Profitabilitas dan Kepemilikan Institusional Terhadap Kebijakan Hutang Pada Perusahaan Otomotif Periode 2012-2019 - Muhammad Rivandi; Vega Putri Rahmadani (Fakultas Sastra Universitas Ekasakti, 2021)
The debt policy is a policy regarding the reduction or addition of debt by the company's management to obtain a source of financing for the company's operations. This study aims to examine the effect of asset structure, profitability and institutional ownership on debt policy. The sample of this study were seven automotive companies listed on the Indonesia Stock Exchange (BEI) for the period 2012-2019 which were selected using purposive sampling method. The data analysis method used in this study is a panel regression model. Based on the results of hypothesis testing, that the asset structure has a significant positive effect on debt policy, while profitability and institutional ownership have a negative and significant effect on debt policy.